Risk of venous thromboembolism in patients with idiopathic pulmonary fibrosis: a systematic review and meta-analysis - Boonpheng, Boonphiphop; Ungprasert, Patompong (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: Recent studies have suggested that patients with idiopathic pulmonary fibrosis (IPF) may have a higher risk of venous thromboembolism (VTE) compared to general population even though the results were inconsistent. Objective: To investigate the risk of VTE among patients with IPF. Methods: Comprehensive literature review using MEDLINE and EMBASE database were performed to identify studies that compared the risk of VTE among patients with IPF to general population. Effect estimates from each study were combined together using random effect model, generic inverse variance method of DerSimonian and Laird. Results: Out of 510 retrieved articles, 5 studies met the inclusion criteria and were included in the meta-analysis. A significant risk of VTE in patients with IPF was observed with the pooled risk ratio of 2.11 (95% confidence interval, 1.28-3.48). The heterogeneity was moderate with I2 of 64%. Conclusion: An approximately 2-fold increased risk of VTE among patients with IPF was observed in this meta-analysis.